Antiviral Combination Clinically Better Than Standard Therapy in Severe but Not in Non-Severe COVID-19 - Panda PK; Singh BO; Moirangthem B; Bahurupi YA; Saha S; Saini G; Dhar M; Bairwa M; Pai VS; Agarwal A; Sindhwani G; Handu S; et al. (Dove Medical Press, 2021)
Prasan Kumar Panda,1 Budha O Singh,1 Bikram Moirangthem,1 Yogesh Arvind Bahurupi,2 Sarama Saha,3 Girraj Saini,4 Minakshi Dhar,1 Mukesh Bairwa,1 Venkatesh Srinivasa Pai,1 Ankit Agarwal,5 Girish Sindhwani,6 Shailendra Handu,7 Ravi Kant8 1Department of Medicine (Infectious Disease Division), All India Institute of Medical Sciences (AIIMS), Rishikesh, India; 2Department of Community and Family Medicine, All India Institute of Medical Sciences (AIIMS), Rishikesh, India; 3Department of Biochemistry, All India Institute of Medical Sciences (AIIMS), Rishikesh, India; 4Department of Nursing, All India Institute of Medical Sciences (AIIMS), Rishikesh, India; 5Department of Critical Care Medicine, All India Institute of Medical Sciences (AIIMS), Rishikesh, India; 6Department of Pulmonary Medicine, All India Institute of Medical Sciences (AIIMS), Rishikesh, India; 7Department of Pharmacology, All India Institute of Medical Sciences (AIIMS), Rishikesh, India; 8Department of General Surgery, All India Institute of Medical Sciences (AIIMS), Rishikesh, IndiaCorrespondence: Prasan Kumar PandaDepartment of Medicine (Infectious Disease Division), All India Institute of Medical Sciences (AIIMS), Sixth Floor, College Block, Rishikesh, 249203, IndiaTel +91 9868999488Email motherprasanna@rediffmail.comPurpose: Definitive antiviral treatment is not available for COVID-19 infection, with the exception of remdesivir, which still evokes many doubts. Various monotherapy or combination therapies with antivirals or other agents have been tried. The present study aims to evaluate the therapeutic potential of hydroxychloroquine and lopinavir-ritonavir in combination with ribavirin in mild-severe COVID-19.Patients and Methods: A single-center, open-label, parallel-arm, stratified randomized controlled trial evaluated the therapeutic potential of combination antiviral therapies. Enrolled patients in the severe category were randomized into three groups: (A) standard treatment, (B) hydroxychloroquine+ribavirin+standard treatment, or (C) lopinavir+ritonavir+ribavirin+standard treatment; while the non-severe category comprised two groups: (A) standard treatment or (B) hydroxychloroquine+ribavirin. Combination antivirals were given for 10 days and followed for 28 days. The primary endpoints were safety, symptomatic and laboratory recovery of organ dysfunctions, and time to SARS-CoV-2 RT-PCR negative report.Results: In total, 111 patients were randomized: 24, 23, and 24 in severe categories A, B, and C, respectively, and 20 in each of the non-severe groups. Two patients receiving ribavirin experienced drug induced liver injury, and another developed QT prolongation after hydroxychloroquine. In the severe category, 47.6%, 55%, and 30.09% in A, B, and C groups, respectively, showed symptomatic recovery, compared to 93.3% and 86.7% in A and B groups, respectively, in the non-severe category at 72 hours (P> 0.05).Conclusion: Though the results failed to show statistical superiority of the antiviral combination therapies to that of the standard therapy in both the severe and non-severe categories in symptomatic adult patients of COVID-19 due to very small sized trial, clinically hydroxychloroquine+ribavirin therapy is showing better recovery by 7.4% than standard therapy in the former category. However, results do indicate the benefit of standard therapy in the non-severe category by 6.6%. Furthermore, the dose of ribavirin needs to be reconsidered in the Indian population.Keywords: coronavirus disease 2019, interventional trial, hydroxychloroquine, lopinavir/ritonavir combination, ribavirin